The mission song [compact disc, unabridged] - Le Carré, John, 1931-2020- (Hodder & Stoughton Audiobooks, 2006)
After being abandoned by both his Irish father and Congolese mother, Bruno Salvador's life is guided by a British Intelligence officer. He becomes an interpreter and stumbles upon a nasty plot and ends up courting danger from London to Congo to an island off Denmark.